Pattern of Microorganisms Isolated from Endotracheal Swabs of Neonates and Determination of Their Antibiotic Susceptibility (Medical Forum Monthly, 2021)
Objective: The aim of this study was to identify the microorganisms that colonize the trachea of intubated neonates at 1st, 24th, 48th and 72nd hours of intubation and find their antibiotic sensitivity pattern.Study Design: Descriptive case series studyPlace and Duration of Study: This study was conducted at the Department of Pediatric Medicine Unit II, Mayo Hospital Lahore. Study duration was 2 years from August 2014 to July 2016.Materials and Methods: This study was conducted on 189 neonates who remained intubated for more than 72 hours at the hospital. After data collection, data were processed and analyzed using statistical software SPSS, version 20.Results: When total sample collection events (1st, 24th, 48th and 72nd hours) were considered to be 100%, the majority showed no growth (65%), whereas in positive cultures Pseudomonas topped the list with 19% positive cultures followed by E.coli (6%) and Coagulase positive Staph aureus (6%). Antibiotics resistance was most commonly seen for ampicillin and cefotaxime, 5.2% each, while most bacteria were sensitive to vancomycin, tanzo and meropenem (5.2%) each.Conclusion: Pseudomonas is the most common bacteria causing ventilator-induced pneumonia among neonates.